If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(20+3)=-3(a-1)+31
We move all terms to the left:
4(20+3)-(-3(a-1)+31)=0
We add all the numbers together, and all the variables
-(-3(a-1)+31)+423=0
We calculate terms in parentheses: -(-3(a-1)+31), so:We get rid of parentheses
-3(a-1)+31
We multiply parentheses
-3a+3+31
We add all the numbers together, and all the variables
-3a+34
Back to the equation:
-(-3a+34)
3a-34+423=0
We add all the numbers together, and all the variables
3a+389=0
We move all terms containing a to the left, all other terms to the right
3a=-389
a=-389/3
a=-129+2/3
| −3/4(x+7)=36 | | 15m+16=46 | | 3(5y-7)=39 | | m-1=3/4 | | 4=64x | | 12=6+2a | | 5/8y-3=18 | | -5(3x-27)=2(x-18)-33 | | 5(5x-3)+6=-5 | | -3+5=2x-15 | | 274=-8x+4 | | 60=11.3x+19 | | 11x+8=-2(5x-4) | | 20=5a-15 | | w/3-8=16 | | x-4/7=150 | | v^2-v-40=0 | | 3a-8=2+a | | 36=3v | | 25000-2500x=10000 | | 20x=10+50x | | n/10-2=8 | | 3x+1=x+11=180 | | 6(x+3=5x+8 | | 14/15=45/x | | 2y-2/4-6+7/3=0 | | 2x=3x-26=180 | | 6=4a-24 | | 40+5x=4(-x+3)-44 | | X*3x=6689 | | -6x+20x=20x-1 | | 3(4-4y)=18-9y |